The surgical resection of the primary tumor increases survival in patients with EGFR-mutant advanced non-small cell lung cancer: a tertiary center cohort study - Ying-Yuan Chen; Po-Lan Su; Wei-Li Huang; Chao-Chun Chang; Yi-Ting Yen; Chien-Chung Lin; Yau-Lin Tseng (Scientific Reports, 2022)
Abstract Tumor resection could increase treatment efficacy of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI) in patients with advanced EGFR-mutant non-small cell lung cancer (NSCLC). This study aimed to retrospectively analyze patients with advanced EGFR-mutant NSCLC from a Taiwanese tertiary center and receiving EGFR-TKI treatment with or without tumor resection. A total of 349 patients were enrolled. After propensity score matching, 53 EGFR-TKI treated patients and 53 EGFR-TKI treated patients with tumor resection were analyzed. The tumor resection group showed improved progression-free survival (PFS) (52.0 vs. 9.8 months; hazard ratio [HR] = 0.19; p < 0.001) and overall survival (OS) (not reached vs. 30.6 months; HR = 0.14; p < 0.001) compared to the monotherapy group. In the subgroup analysis of patients with newly-diagnosed NSCLC, the tumor resection group showed longer PFS (52.0 vs. 9.9 months; HR = 0.14; p < 0.001) and OS (not reached vs. 32.6 months; HR = 0.12; p < 0.001) than the monotherapy group. In conclusion. the combination of EGFR-TKI and tumor resection provided better PFS and OS than EGFR-TKI alone, and patients who underwent tumor resection within six months had fewer co-existing genomic alterations and better PFS.